SOVIET-ERA TAX POLICY - Mamadjanova Dildora,; Jabbarov Asilbek, (TADQIQOTLAR, 2025)
Abstract This article provides an in-depth analysis of the tax policy implemented during the Soviet Union. It explores the role of taxes in shaping the state budget within a centrally  planned  economy,  their  function  in  controlling  the  population,  and  the methodologies  aimed  at  ensuring  social  equality.  The  relevance  of  tax  policy,  its methodological approaches, and key findings are examined in historical, economic, and ideological contexts. The article highlights the unique features of the Soviet tax system — its reliance on planning, progressive taxation, strict limitations on private ownership, and mechanisms for monitoring personal income. These historical practices offer valuable lessons for the improvement of modern tax policies.